Participación comunitaria y legislación en El Salvador. Análisis de la legislación identificada - Cortez Juárez, Guillermo (2008)
Community participation has been considered strategic in order to achieve effectiveness in political, economical, social, educational and cultural change processes as a mean of guarantying effectiveness, quality and sustainability in social policy. Accordingly, this participation must be stimulated and promoted through national legislation since it has traditionally and historically been imposed and undemocratic. Education, as an essentially human act, is a first order instrument that societies must take advantage of in order to develop and stimulate democratic participation. Therefore, education may represent a new culture: one of democratic participation as a fundamental way to empower and develop a Peace culture.